Serum sphingomyelin species profile is altered in hematologic malignancies - Hori, Atsushi; Ishida, Fumihiro; Nakazawa, Hideyuki; Yamaura, Makoto; Morita, Sunao; Uehara, Takeshi; Honda, Takayuki; Hidaka, Hiroya (Clinica chimica acta, 2021)
•The sphingomyelin species from B-cell lymphoma, MDS, AML and ALL/LBL patients was analyzed by mass spectrometry.•The SM profiles differed between four types of hematologic malignancy patients.•SM species containing saturated odd chain fatty acid from patients was lower levels compared to normal serum.•SM species containing long-chain fatty acid from MDS patients was lower levels compared to other patients. Sphingomyelin (SM) plays key roles in regulating cell membrane fluidity and in intracellular signal transduction. However, little is known as to whether alterations in SM concentration or SM species distribution are linked pathological conditions. The present study examined SM concentrations and species profiles in serum taken from patients with hematologic malignancies. Serum was collected from normal subjects and from patients with B-cell lymphoma, myelodysplastic syndrome (MDS), acute myeloid leukemia (AML) and acute lymphatic leukemia/ lymphoblastic lymphoma (ALL/LBL). Serum SM species distribution was analyzed using electrospray ionization mass spectrometry/ mass spectrometry (ESI MS/MS). Serum lipids concentration were measured using enzymatic assays. Normal and hematologic malignancy sera were similar in terms of total serum SM and phosphatidylcholine (PC) concentrations and SM/PC ratio. However, all hematologic malignancy sera had lower levels of SM species containing saturated odd chain fatty acids (OCFAs) in the side chain compared to normal serum. In addition, the proportion of SM species with saturated (C20 and C22) and mono unsaturated fatty acids (C18, C20, C22) were lower in MDS patient serum compared to normal serum. The present study revealed that the serum SM species profile in patients with hematologic malignancies differed from that of normal subjects despite total serum SM and PC concentrations and SM/PC ratios being similar between the various cancer groups and the normal group.